TINJAUAN PELAKSANAAN PERHITUNGAN, PEMOTONGAN, DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 PADA PT. INTOTU INTEGRATOR NIAGA - Yunindah Dewi Sarih (2022)
Taxation is one of the largest foreign currency earners in Indonesia. So far, tax revenues have been dominated by personal income tax on employees and non-employees. Regulations on income tax collection in Indonesia Income Tax Article 21 (PPh 21). Income tax Article 21 is a tax levied on income from salaries, wages, fees, allowances and other payments earned by residents. Public and private employees are one of the goals of income tax collection. In this case, the income received by each employee of PT Intotu Integrator Niaga will be deducted according to the provisions contained in Article 21 Income Tax. The purpose of writing this scientific paper is to review the system for calculating, withholding, and depositing Income Tax Article 21 to employees. PT Intotu Integrator Niaga.